Draft Annual Plan 1989-90 Volume : VI General Areas Government of Assam - Planning Commission (Planning Commission, 1989)
India is signatory to Alma Ata declaration committing to attain the goal of "Health for All by the year 2000 A.D." and it is proposed to achieve the goal through primary health care system by providing universal comprehensive primary health care services relevant to the actual need and priority of the community at a cost which people can afford and through active participation of the community.
Government of Assam, Planning and Development Department